Talon cusp associated with other dental anomalies: a case report - J. K. DASH, P. K. SAHOO & S. N. DAS (Paediatric Dentistry, 2004)
Talon cusp is an uncommon dental anomaly referring to an accessory cusp projecting from the cingulum area, or cemento-enamel junction of maxillary or mandibular anterior teeth, in both the primary and permanent dentition.